ANALYSIS OF THE ENERGY EFFICIENCY OF THE DISTRIBUTION ELECTRIC NETWORKS OF THE VILLAGE NESHKAN OF THE CHUKOTKA REGION - N.V. Pikul; N.S. Buryanina (Zenodo, 2022)
Energy consumption is considered a prerequisite for the existence of modern society. The article deals with improving the quality of electrical energy for consumers and reducing its losses in the electrical networks of a remote and hard-to-reach Arctic village located in the Chukotka region. To solve the problem, it is proposed to evenly distribute the loads across feeders and phases, shorten the length of overhead lines, install a step-up complete transformer substation, and use self-supporting insulated wires.